Nitrogen translocation in wheat inoculated with Azospirillum and fertilized with nitrogen - Rodrigues, Osmar; Didonet, Agostinho Dirceu; Gouveia, Jorge A.; Soares, Rita de Cassia (Pesquisa Agropecuaria Brasileira, 2000)
The productivity and the translocation of assimilates and nitrogen (N) were compared after inoculation of wheat (Triticum aestivum L., cv. BR-23) seeds with two strains of Azospirillum brasilense (strains 245 and JA 04) under field conditions. The inoculation of wheat seeds was done with a peat inoculant at sowing time. Plant material for evaluations were collected at anthesis and maturity. No differences in grain yield and in the translocation of assimilates resulting from inoculation were detected. Differences were observed in relation to N rates (0, 15, and 60 kg ha-1). N content in the grain increased significantly in the bacteria-inoculated treatments in which N was not added. This increase in N content in the grain with inoculation was probably due to higher N uptake after anthesis without any significant contribution on the grain yield. Such increment was of 8.4 kg ha-1 of N representing 66% more N than in no inoculated treatment. Regardless of the inoculation and the rate of N applied, it was observed that about 70% of the N accumulated at anthesis was translocated from vegetative parts to the grain.